Application of Stir Tool Force Measuring Dynamometer for Friction Stir Welding of Aluminum Alloys - Wang, H.F.; Wang, J.L.; Zuo, D.W.; Song, W.W. (Проблемы прочности, 2017)
In this study, a stir tool force measuring dynamometer was designed and manufactured to be suitable for use during the process of friction stir welding. The dynamometer meets the requirements needed for actual force measurements, with error percentage values in the x-, y-, and z-axis directions of 1.1, I.3, and 1.2%, respectively, and a three-directional sensitivity range of 0.4-2.1%. At the same time, stir tool forces were measured under different process parameters using the manufactured dynamometer. The stir tool force mathematical model, to be used for friction stir welding processes, was established by function approximation and regression analysis methods. The model was set up with a significance level under 90%. Finally, a comparison between the model-calculated values and experimental values yielded a stir tool force average error of 10.4, 4.66,, and 7.11% in the x, y, and z axes direction, respectively. Therefore, calculated and experimental values are in agreement.